Ethnoecology and Medicinal Plants of the Highland Maya - Stepp, John Richard (Ethnobiology, 2018)
Plants play a central role in human existence. Medicinal plants, in particular, have allowed for the continued survival of the human species. This book, based on over a decade of research in Southern Mexico with the Highland Maya, explores the relationship between medicinal plants, traditional ecological knowledge and the environment. The biodiversity of the region remains among the highest in the world, comprising more than 9000 plant species. Over 1600 employed for medicinal uses and knowledge for approximately 600 species is widespread. Medicinal plants play an overwhelmingly primary role in the daily health care of the Highland Maya. Three principal objectives are addressed: 1) identifying which medicinal plants are used; 2) determining the role of environmental variation on use and selection of medicinal plants; and 3) identifying which habitats are preferred for medicinal plant procurement. Findings demonstrate the overwhelming importance of human modified environments for medicinal plants. Explanations are presented from human ecology and biochemical ecology. Implications for conservation, health and the environment are discussed.